Pentingnya Remaja Putri Memiliki Pengetahuan yang Baik dalam Mengendalikan Kecemasan Menghadapi Disminorea Primer - R Tri Rahyuning Lestari; Gilang Rahmatulloh; Junaida Rahmi; Akub Selvia; Maelia Unayah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the relationship between the level of knowledge and anxiety in young women dealing with primary dysmenorrhea. The method used is a quantitative approach with a cross-sectional research design. The number of samples in this study was 40 young women. The results showed a relationship between the level of knowledge and anxiety of young women dealing with primary dysmenorrhea in Depok, with a p-value of 0.001. Young women need to have good knowledge in dealing with primary dysmenorrhea so that it will reduce the anxiety they feel. This study concludes that increasing the understanding of young women regarding the prevention of primary dysmenorrhea can minimize the stress level experienced by young women. Keywords: Dysmenorrhea, Anxiety, Knowledge, Young Women